The classroom problems of teachers of the first cycle of basic education in treating in the city of Latakia from their point of view. - صبّوح, نسرين (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Summary of the research in Arabic: The research aimed to identify the role of teachers of the first cycle of basic education in treating classroom problems in the city of Latakia from their point of view. The research adopted the descriptive analytical approach to reach the specific objectives. The original community consisted of teachers working in the Lattakia Education Directorate, numbering (50) male and female teachers as a random sample. The questionnaire was applied to them as the main tool for the research. The results indicated that: There are no statistically significant differences between the average scores of teachers’ opinions about teachers’ classroom problems due to the variable of gender and experience in teaching.